The effects of vaporization on the respiratory, cardiovascular, skin, oral and dental systems - Załęski, Daniel; Zdebski, Paweł; Ejsner, Rafał; Marzec , Urszula; Grabiński , Jakub; Dmowska, Dominika; Gloc, Ewa (Quality in Sport, 2026)
Introduction: Vaping, defined as the inhalation of an aerosol generated by electronic nicotine delivery systems (ENDS), has become a rapidly growing public health phenomenon, particularly among adolescents and young adults. Despite the absence of a combustion process, e-cigarettes deliver nicotine along with numerous chemical compounds with potential toxic properties, raising concerns regarding their multisystem health effects. Materials and Methods: A narrative–systematic review of the literature published between 2013 and 2025 was conducted. Publications indexed in PubMed, JAMA Network, ScienceDirect, Wiley Online Library, as well as reports from international institutions, were analyzed. Results: E-cigarette use has been shown to be associated with multisystem health effects. Within the respiratory system, symptoms such as cough, dyspnea, wheezing, exacerbations of asthma and chronic obstructive pulmonary disease (COPD), as well as cases of acute lung injury (EVALI), have been reported. In the cardiovascular system, endothelial dysfunction, increased arterial blood pressure, and oxidative stress have been observed. Cutaneous manifestations include impaired wound healing and inflammatory processes. In the oral cavity, an increased risk of periodontal disease, dental caries, and microbiome dysbiosis has been identified. Discussion: Available evidence suggests that e-cigarettes exhibit biological activity and may induce multisystem health consequences. Although the levels of certain toxicants may be lower than those found in conventional tobacco smoke, this does not imply safety. A key limitation remains the lack of long-term population-based studies. Conclusions: Vaping is associated with significant health risks affecting multiple organ systems. Current evidence does not support its safety, and the use of e-cigarettes should be considered potentially harmful. Further research and preventive measures are warranted, particularly among adolescent populations.